Plan de marketing para el posicionamiento del Hotel el Brujo SAC - Trujillo 2014 - Valdivia Alfaro, Cathereine Gissela (2014)
The present work of investigation was elaborated by the purpose of allowing the positioning of the Company Hotel El Brujo SAC –Trujillo. With the determination of this work, the company will put emphasis to the raised problem: in what measure the Marketing plan there will allow the positioning of the Hotel El Brujo SAC de la ciudad Trujillo 2014? For the present research report the design was in use not experimental - transeccional, statistician; and a survey was applied as technology of investigation. In the survey applied to the clients of the Company Hotel The Wizard SAC - Trujillo, we can highlight that the Strategies of marketing influence the positioning of the clients doing that this one is the most suitable. As conclusion of the same one the production of the Marketing plan of the Hotel The Wizard SAC, has allowed to define his positioning from the perception of the clients. To this respect the Hotel The Wizard, is positioned as an establishment of cozy accomodations of comfortable facilities and with an important offer of complementary services.